Development of Village Apparatuses in the Field of Village Government Management in Pauh Angit Village, Pangean District, Kuantan Singingi Regency - Iskandar Iskandar; Hendrayani Hendrayani; Jonni Ardan Mardan; Eka Putra; Muh. Ali Aqsa; Risman Risman (CV. Rayyan Dwi Bharata, 2023)
The purpose of this community service is to assist local governments in realizing village development planning, governance, and a good village financial management system through activities in providing organizational training and motivation of village officials in the field of village governance generally in Pauh Angit Village and especially in Pangean District. Kuantan Singingi Regency. This activity was carried out in the form of training and motivation for village officials regarding the Village Government System to improve Village capabilities in realizing village community empowerment. The results of this training and motivational activity can be said to have been successful in the presence of government officials from the Pauh Angit village in Pangean District. This can be seen from the percentage of participants' attendance and the enthusiasm of the participants during the activity.